Α-Lactalbumin peptide Asp-Gln-Trp alleviates hepatic insulin resistance and modulates gut microbiota dysbiosis in high-fat diet-induced NAFLD mice. Issue 19 (2nd September 2022) - Chen, Haoran; Sun, Yue; Zhao, Haiding; Qi, Xiaofen; Cui, Hui; Li, Qiming; Ma, Ying
Abstract : α-Lactalbumin peptide Asp-Gln-Trp (DQW) alleviates hepatic insulin resistance via activating the IRS1/PI3K/AKT pathway and modulates gut microbiota dysbiosis in high-fat diet-induced NAFLD mice. Abstract : The progression of nonalcoholic fatty liver disease (NAFLD) is closely related to insulin resistance and gut microbiota. Dietary interventions have emerged as effective palliative strategies for NAFLD. The present study investigated the potential mechanisms by which α-lactalbumin peptide Asp-Gln-Trp (DQW) ameliorated insulin resistance and gut microbiota dysbiosis in high-fat diet (HFD)-induced NAFLD mice. The results demonstrated that DQW treatment alleviated HFD-induced body weight gain, hepatic steatosis, insulin resistance, and dyslipidemia. DQW treatment also increased the ratio of Bacteroides to Firmicutes in the gut, reduced the relative abundance of pathogenic bacteria (such as Bacteroides, Blautia, and Alistipes ) and enhanced the relative abundance of short-chain fatty acid (SCFA)-producing bacteria (such as Muribaculaceae, Lachnospiraceae_NK4A136_group, and Rikenellaceae_RC9_gut_group ). DQW treatment promoted the production of SCFAs and subsequently improved intestinal barrier integrity and inflammation. Furthermore, the results of real-time quantitative PCR (qRT-PCR) and western blotting further proved that the effects of DQW on the attenuation of hepatic insulin resistance were mediated by the PPARα and IRS1/PI3K/AKT pathways. Taken together, these results indicated that DQW treatment could attenuate HFD-induced NAFLD and insulin resistance by modulating gut microbiota composition, enhancing the SCFA levels, and activating the PPARα and IRS1/PI3K/Akt pathways.